2013
DOI: 10.1093/gbe/evt172
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics Approaches to Deciphering a Hypervirulent Strain of Campylobacter jejuni

Abstract: Campylobacter jejuni clone SA recently emerged as the predominant cause of sheep abortion in the United States and is also associated with foodborne gastroenteritis in humans. A distinct phenotype of this clone is its ability to induce bacteremia and abortion. To facilitate understanding the pathogenesis of this hypervirulent clone, we analyzed a clinical isolate (IA3902) of clone SA using multi-omics approaches. The genome of IA3902 contains a circular chromosome of 1,635,045 bp and a circular plasmid of 37,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 82 publications
2
61
0
Order By: Relevance
“…Epidemiological analysis of historical clone SA isolates suggested that its emergence in the United States is likely to be a recent event (15), but the genetic basis for its emergence and enhanced virulence is unknown. To facilitate understanding the pathogenesis, we sequenced a representative clone SA isolate (IA3902), which revealed that the genome of IA3902 is highly syntenic to that of C. jejuni strain NCTC11168 (18). Importantly, C. jejuni NCTC11168 was shown to be nonabortifacient in pregnant animals (17), providing a closely related control strain for elucidating the hypervirulence of clone SA.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…Epidemiological analysis of historical clone SA isolates suggested that its emergence in the United States is likely to be a recent event (15), but the genetic basis for its emergence and enhanced virulence is unknown. To facilitate understanding the pathogenesis, we sequenced a representative clone SA isolate (IA3902), which revealed that the genome of IA3902 is highly syntenic to that of C. jejuni strain NCTC11168 (18). Importantly, C. jejuni NCTC11168 was shown to be nonabortifacient in pregnant animals (17), providing a closely related control strain for elucidating the hypervirulence of clone SA.…”
Section: Significancementioning
confidence: 99%
“…Comparative genomics revealed numerous genetic differences between the genomes of IA3902 and NCTC11168, including 57 unique genes and >8,000 SNPs as well as small (<10 bp) insertions and deletions (indels). Transcriptomic and proteomic analyses identified multiple differences in the expression of genes involved in several classical virulence-related pathways: iron acquisition, capsule biosynthesis, energy metabolism, and motility (18). However, the causative genetic changes driving clone SA's success in causing disease remained undetermined.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that clone SA has emerged as a zoonotic pathogen, causing human gastroenteritis linked mainly to the consumption of raw milk (13). The genome of a representative of this clone, C. jejuni IA3902, has now been sequenced (15).…”
mentioning
confidence: 99%